Synthesis of stochastic algorithms for image registration by the criterion of maximum mutual information - A.G. Tashlinskii; G.L. Safina; R.M. Ibragimov (Компьютерная оптика)
We discuss a synthesis of stochastic algorithms, obtaining expressions for gradients of Shannon, Renyi and Tsallis mutual information on the basis of the mathematical apparatus of stochastic gradient adaptation of algorithms for estimating image registration parameters. To obtain the expressions, derivatives of the image entropy with respect to the estimated parameters are used. The entropies are calculated using a Parzen window method. A comparative study of the synthesized algorithms in terms of stability and accuracy of the registration parameter estimates, including in conditions of additive noise, is carried out.